Life-course determinants of cognitive reserve (CR) in cognitive aging and dementia – a systematic literature review. (3rd August 2018) - Chapko, Dorota; McCormack, Roisin; Black, Corri; Staff, Roger; Murray, Alison
ABSTRACT: Objectives : The concept of cognitive reserve (CR) is defined as a moderator, which allows an individual to preserve cognition despite underlying brain pathology. There is no consensus of what potentially modifiable CR determinants are of greatest importance. The aim of this review was to identify life-course factors which protect older individuals from expressing cognitive decline despite the presence of brain pathology. Method : A systematic review search was performed in MEDLINE (1946–06/09/13), EMBASE (1947–06/09/13), and PsycheInfo (1967–06/09/13). We included studies examining CR in the context of the four commonest subtypes of dementia, mild cognitive impairment or healthy aging. Studies which combined measurement of underlying dementia-related neuropathology, cognitive function, and factors providing CR in a single model were accepted. We performed a qualitative synthesis of the results. Results : Thirty-four studies out of 9229 screened records met our inclusion criteria and were therefore quality assessed and data extracted. Variation in CR definition made comparison across studies difficult. One hundred and forty-four out of 156 models examined education and occupation: overall, 58% of eligible models classified education and 60% occupation as a CR determinant, with 12% and 44% of those, respectively, being of high quality. Within healthy population suitable to inform preventative interventions, there was consistent evidence for education having a protective effect on general cognition in the face of multiple brain burden measures, while occupation presented inconclusive results within cognitive groups. Conclusions : Further research on modifiable determinants of CR beyond education/occupation including early-life factors and consensus on CR definition are warranted.